Silk scaffolds connected with different naturally occurring biomaterials for prostate cancer cell cultivation in 3D. Issue 2 (February 2017) - Bäcker, Anne; Erhardt, Olga; Wietbrock, Lukas; Schel, Natalia; Göppert, Bettina; Dirschka, Marian; Abaffy, Paul; Sollich, Thomas; Cecilia, Angelica; Gruhl, Friederike J.
Abstract: In the present work, different biopolymer blend scaffolds based on the silk protein fibroin from Bombyx mori (BM) were prepared via freeze‐drying method. The chemical, structural, and mechanical properties of the three dimensional (3D) porous silk fibroin (SF) composite scaffolds of gelatin, collagen, and chitosan as well as SF from Antheraea pernyi (AP) and the recombinant spider silk protein spidroin (SSP1) have been systematically investigated, followed by cell culture experiments with epithelial prostate cancer cells (LNCaP) up to 14 days. Compared to the pure SF scaffold of BM, the blend scaffolds differ in porous morphology, elasticity, swelling behavior, and biochemical composition. The new composite scaffold with SSP1 showed an increased swelling degree and soft tissue like elastic properties. Whereas, in vitro cultivation of LNCaP cells demonstrated an increased growth behavior and spheroid formation within chitosan blended scaffolds based on its remarkable porosity, which supports nutrient supply matrix. Results of this study suggest that silk fibroin matrices are sufficient and certain SF composite scaffolds even improve 3D cell cultivation for prostate cancer research compared to matrices based on pure biomaterials or synthetic polymers.